Liquid range temperature of ionic liquids as potential working fluids for absorption heat pumps. (December 2015) - Villanueva, M.; Parajó, J.J.; Sánchez, Pablo B.; García, J.; Salgado, J.
Highlights: Liquid range was determined for 6 ILs with 3 different cations and 4 anions. Pyridinium ILs presented the highest melting points and imidazolium the lowest. ILs present high thermal stability, with onset temperatures higher than 300 °C. Long-term thermal stability temperatures are higher than 200 °C for all ILs. Ageing does not produce any detectable changes in ILs thermal behaviour. Abstract: The liquid range temperature of six ionic liquids (ILs) was determined in this work with the aim to propose suitable absorbents for heat pump systems. The selected ILs have three different cations, imidazolium, pyridinium and choline and each was combined with four different anions [NTf2 ] −, [OTf] −, [MeSO3 ] − and [BETI] − . The lower limit, given by solid − liquid transitions, was determined using differential scanning calorimetry (DSC). The upper limit is given by the degradation temperature. This temperature is determined using thermogravimetric technique (TGA). Dynamic and isothermal methods have been combined to estimate the maximum operation temperature. ILs ageing effect was also analysed in this work.